What has happened to EUSS applications from Wales since June 2021? - Stephen J. Drinkwater; Matt Curds; Ffion Lloyd-Williams (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
One of the outcomes of the Brexit referendum result was that EU nationals were required to register on the EU Settlement Scheme (EUSS) if they wanted to remain in the UK after its departure from the EU. In order to be granted settled or pre-settled status, applications needed to have been submitted by 30th June 2021. However, applications continue to have been submitted and processed after this date because of late applications (with a reasonable explanation), transfers from pre-settled to settled status and family members wishing to join relatives in the UK. Published Home Office statistics provide only limited information on applications received since June 2021 separately for the countries in the UK, which is not that helpful for devolved governments. In this paper, we apply a simple method to calculate applications received after June 2021 from the four countries in the UK, focusing particularly on applications for several demographic subgroups from Wales. Our results show increases in applications from Romanian and Bulgarian nationals since June 2021 as well as rises in refused, withdrawn and invalid applications. We also find that a relatively high percentage of recent applications were made by people living in Newport since this local authority accounted for around 18% of the Welsh total after June 2021 compared to 11% before this.
Keywords: K37; F22; J61; 330; EU Nationals; Settlement Scheme; Brexit; United Kingdom; Wales